2012
DOI: 10.1016/j.bbagen.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Different fractions of human serum glycoproteins bind galectin-1 or galectin-8, and their ratio may provide a refined biomarker for pathophysiological conditions in cancer and inflammatory disease

Abstract: Background: Changes in glycosylation of serum proteins are common, and various glycoforms are being explored as biomarkers in cancer and inflammation. We recently showed that glycoforms detected by endogenous galectins not only provide potential biomarkers, but also have different functions when they encounter galectins in tissue cells. Now we have explored the use of a combination of two galectins with different specificities, to further increase biomarker sensitivity and specificity. less thanbrgreater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Second, galectin-8N has a particularly high affinity for ␣2,3-sialylated ␤-galactosides present in the common core-1 O-glycan structure (29). This binding pattern can also be seen for serum glycoproteins, where galectin-8N binds a large fraction of the heavily O-glycosylated IgA1, without binding N-glycosylated IgM; galectin-1 shows the opposite profile (30). The future generation of cells lacking both O-linked glycans, N-linked glycans, and glycosphingolipids will enable further clarification of the individual role of each class of glycans in galectin binding.…”
Section: Galectin Glycan-binding In a Natural Contextmentioning
confidence: 95%
See 2 more Smart Citations
“…Second, galectin-8N has a particularly high affinity for ␣2,3-sialylated ␤-galactosides present in the common core-1 O-glycan structure (29). This binding pattern can also be seen for serum glycoproteins, where galectin-8N binds a large fraction of the heavily O-glycosylated IgA1, without binding N-glycosylated IgM; galectin-1 shows the opposite profile (30). The future generation of cells lacking both O-linked glycans, N-linked glycans, and glycosphingolipids will enable further clarification of the individual role of each class of glycans in galectin binding.…”
Section: Galectin Glycan-binding In a Natural Contextmentioning
confidence: 95%
“…Past studies have shown that both N-and mucin type O-glycans act as ligands for galectins, although the vast majority of the published data report complex N-glycans as the primary interaction partners (22,30,(35)(36)(37). To determine the contributions of N-and O-linked glycans as ligands for the individual galectins, we probed the binding of galectins to CHO cells and EPO with or without complex-type N-linked glycans and with and without core-1 O-linked glycans.…”
Section: N-glycans Versus Mucin Type O-glycansmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that a fraction (ϳ5%) of normal transferrin is bound by galectin-3 (9), a member of a protein family defined by affinity for ␤-galactoside containing glycans, such as found in transferrin. Altered glycosylations are a hallmark of oncogenic transformation (10), and have been shown to alter galectin binding of glycoproteins (11)(12)(13). Galectin-3, like other galectins, has diverse roles in cancer, inflammation, and development (14), and one cellular mechanism for this is that it regulates the intracellular traffic of certain cellular glycoproteins by binding their glycans (11,13,15,16).…”
mentioning
confidence: 99%
“…GAL1 may provide a novel candidate target for pancreatic cancer (10). Interestingly, the galectin-binding ability of a glycoprotein is not only a promising biomarker candidate but also may be related to the pathophysiological state of the patient (11). In addition, the interaction between cancer cells and their microenvironment is a vicious cycle that enhances the survival and progression of cancer, resulting in metastasis.…”
Section: Introductionmentioning
confidence: 99%